Central bacterial corneal ulcers of prolonged course. Immunological aspects and tactics of etiopathogenetic treatment - V. V. Neroev; L. A. Katargina; L. A. Kovaleva; G. I. Krichevskaya; N. V. Balatskaya; I. G. Kulikova (Российский офтальмологический журнал)
Purpose: to describe the characteristic clinical signs and to study the causes of the development of an unfavorable prolonged course of bacterial corneal ulcers of central localization, and to improve treatment effectiveness. Material and methods. A total of 289 patients with central bacterial corneal ulcers were examined. Two types courses of bacterial corneal ulcer were distinguished: favorable (acute and subacute) and unfavorable (prolonged subacute and prolonged chronic forms). Blood (122 samples) and scrapings from corneal ulcers (110 samples) were examined in a nested polymerase chain reaction (PCR) to detect deoxyribonucleic acid (DNA) of simple herpes virus (HSV) 1 and 2 types, virus Epstein–Barr (VEB), human herpes virus (HHV)-6, and HHV-7. To detect autoimmune sensitization to the corneal antigens, migration inhibition reaction of leukocytes (MIRL, 215 samples) was used. Results. In patients with unfavorable course of the disease, blood and corneal HHV DNA was detected in 88.7 % of cases, while with a favorable course only 10 % of cases showed the presence of HHV DNA (р < 0.002). In all patients, HHV type 6 was predominating. Autosensitivity to corneal antigens was detected in 8 (10.4 %) out of 77 patients at the end of the first week of the disease, and as the disease progressed, the number of patients with an autoimmune component increased to reach 63.2 % (48 of 76). The inclusion of antiviral and immunosuppressive drugs into the routine treatment plan led to complete epithelialization of the cornea within 5–10 days. Сonclusion. The protracted course of bacterial corneal ulcers was found to be caused by a mixed herpes-bacterial infection, which is corroborated by the effectiveness of the modified treatment tactics.